Post-stroke driving: Examining the effect of executive dysfunction - Motta, Karen; Lee, Hoe; Falkmer, Torbjorn (Pergamon, 2014)
Introduction: Executive dysfunction can refer to both neurocognitive deficits and behavioral symptoms that include impaired judgment, slow decision making, disorganization, impulsiveness, and risk-taking behaviors. Executive dysfunction is relatively common in the post-stroke population but is often undetected. The impact of executive dysfunction on post-stroke driving is unclear but it may pose a risk to affected drivers and other road users. Aim: The aim of this study was to investigate the relationship between executive functioning following stroke and driving performance. Methodology: A case–control study design was used. Purposive sampling was used to recruit stroke participants (n = 19) and healthy controls (n = 22). Participants were screened using a battery of psychometric assessments including the Montreal Cognitive Assessment and the Benton Judgment of Line Orientation. Driving performance was assessed using the STISIM driving simulator. Executive function was assessed using the Behavioural Assessment of the Dysexecutive Syndrome (BADS) and the Trail Making Test Part B.Results: The control participants performed better than the stroke participants on the driving assessment and psychometric assessments. There was an association between the scores of the Trail Making Test Part B (Rho = 0.34, p = 0.034) and the Key Search Test of the BADS (Rho = − 0.61, p = 0.005), and the driving assessment scores. However, there was no association between the overall BADS scores and the driving assessment scores of the stroke participants. Conclusions: The stroke participants underperformed in the driving assessment and the psychometric assessments that detected neurocognitive deficits, which included executive function. The Trail Making Test Part B and Key Search Test of the BADS were related to identify participants' deterioration in driving performance. Practical Applications: In clinical practice, the latter could be used as an indication of a post-stroke driver's performance.